Pengaruh Kualitas Produk Dan Pelayanan Terhadap Kepuasan Konsumen Nasi Goreng 99 Cibinong - Muhamad Arif Juniardi; Leny Muniroh; Imam Sundarta (CV. ITTC INDONESIA, 2022)
This study was carried out at the Nasi Goreng 99 restaurant in Cibinong, Bogor Regency, West Java. In Cibinong, 2023, this research will be conducted. The population in this study consists of 100 average daily Cibinong Fried Rice consumers. The Slovin formula can calculate as many as 50.00 (50) samples. Multiple linear regression is used in data analysis. The outcomes revealed that: (1) The results of the hypothesis test partially supported the idea that product quality affected consumer satisfaction in Nasi Goreng 99 Cibinong with a computed t value more than the table t value (2.502) and a significant value of 0 less than 0.05. (2) With a computed t value more than the table t value (2.456) and a significance value of 0 less than 0.05, the results of the hypothesis test partially demonstrate that customer happiness in Nasi Goreng 99 Cibinong is influenced by service quality. (3) The results of the hypothesis test show that both the variables of product quality and service quality have a positive and significant impact on customer satisfaction in Nasi Goreng 99 Cibinong, with a calculated value of f > f table, specifically 26.141 > 3.19 and a significance value of 0.000 0.05. The service quality variable, which has a regression coefficient of 0.329, is the factor that has the greatest influence on customer satisfaction in Nasi Goreng 99 Cibinong.5Test results for the coefficient of determination (adjusted R2) show a value of 0.506, which indicates a 50.6% influence of the independent variable (X) on the dependent variable (Y). This indicates that the degree of the independent variable's influence on the dependent variable (customer happiness) is 50.6% of consumer satisfaction at Nasi Goreng 99 Cibinong influenced by product quality and service quality. While other elements that were not covered in this study had an impact on the remaining 49.4% of customer satisfaction in Nasi Goreng 99 Cibinong.